Impaired heart rate variability triangular index to identify clinically silent strokes in patients with atrial fibrillation. (25th November 2020) - Haemmerle, P; Eick, C; Bauer, A; Rizas, K.D; Coslovsky, M; Krisai, P; Vesin, J.M; Beer, J; Moschovitis, G; Bonati, L.H; Sticherling, C; Conen, D; et al.
Abstract: Introduction: The identification of clinically silent strokes in patients with atrial fibrillation (AF) is of high clinical relevance as they have been linked to cognitive impairment. Overt strokes have been associated with disturbances of the autonomic nervous system. Purpose: We therefore hypothesize that impaired heart rate variability (HRV) can identify AF patients with clinically silent strokes. Methods: We enrolled 1358 patients with AF without a history of stroke or transient ischemic attack from the multicenter SWISS-AF cohort study who were in sinus rhythm (SR-group, n=816) or AF (AF-group, n=542) on a 5 minute resting ECG recording. HRV triangular index (HRVI), the standard deviation of normal-to-normal intervals (SDNN) and the mean heart rate (MHR) were calculated. Brain MRI was performed at baseline to assess the presence of large non-cortical or cortical infarcts, which were considered silent strokes without history of stroke or transient ischemic attack. We constructed binary logistic regression models to analyze the association between HRV parameters and silent strokes. Results: At baseline, silent strokes were detected in 10.5% in the SR group and 19.9% in the AF group. In the SR-group, HRVI <15 was the only parameter independently associated with the presence of silent strokes (odds ratio (OR) 1.69; 95% confidence interval (CI): 1.04–2.72; p=0.033) after adjustment for various clinical covariates (age, sex, systolic blood pressure, history of hypertension, history of diabetes, history of heart failure, prior myocardial infarction, prior major bleeding, intake of oral anticoagulation, antiarrhythmics or betablockers). Similarly, in the AF-group, HRVI<15 was independently associated with the presence of silent strokes (OR 1.65, 95% CI: 1.05–2.57; p=0.028). SDNN<70ms and MHR<80 were not associated with silent strokes, neither in the SR group, nor in the AF group (Figure). Conclusions: Reduced HRVI is independently associated with the presence of clinically silent strokes in an AF population, both when assessed during SR and during AF. Our data suggest that a short-term measurement of HRV in routine ECG recordings might contribute to identifying AF patients with clinically silent strokes. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Swiss National Science Foundation